2021
DOI: 10.3390/cells11010131
|View full text |Cite
|
Sign up to set email alerts
|

Substrate- and Calcium-Dependent Differential Regulation of Mitochondrial Oxidative Phosphorylation and Energy Production in the Heart and Kidney

Abstract: Mitochondrial dehydrogenases are differentially stimulated by Ca2+. Ca2+ has also diverse regulatory effects on mitochondrial transporters and other enzymes. However, the consequences of these regulatory effects on mitochondrial oxidative phosphorylation (OxPhos) and ATP production, and the dependencies of these consequences on respiratory substrates, have not been investigated between the kidney and heart despite the fact that kidney energy requirements are second only to those of the heart. Our objective was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 121 publications
2
8
0
Order By: Relevance
“…3 ). In line with this, recent results ( 36 ) show that isolated heart and kidney mitochondria exposed to pyruvate plus malate or α-KG plus malate have increased RCRs when in the presence of small increases in Ca 2+ concentrations (in the nanomolar range) but have decreased RCRs when Ca 2+ was further augmented. In contrast, Ca 2+ addition to isolated brain mitochondria energized by pyruvate plus malate leads to reduced RCRs, in a concentration-dependent manner, with no effect on PDH activity ( 37 ).…”
Section: Discussionsupporting
confidence: 73%
“…3 ). In line with this, recent results ( 36 ) show that isolated heart and kidney mitochondria exposed to pyruvate plus malate or α-KG plus malate have increased RCRs when in the presence of small increases in Ca 2+ concentrations (in the nanomolar range) but have decreased RCRs when Ca 2+ was further augmented. In contrast, Ca 2+ addition to isolated brain mitochondria energized by pyruvate plus malate leads to reduced RCRs, in a concentration-dependent manner, with no effect on PDH activity ( 37 ).…”
Section: Discussionsupporting
confidence: 73%
“…3). In line with this, recent results (36) show that isolated heart and kidney mitochondria exposed to pyruvate plus malate or α-ketoglutarate plus malate have increased RCRs when in the presence of small increases in Ca 2+ concentrations (in the nanomolar range), but had decreased RCRs when Ca 2+ was further augmented. In contrast, Ca 2+ addition to isolated brain mitochondria energized by pyruvate plus malate leads to reduced RCRs, in a concentration-dependent manner, with no effect on PDH activity (37).…”
Section: Discussionsupporting
confidence: 73%
“…The OGDC consists of three enzymes: oxoglutarate dehydrogenase (EC 1.2.4.2; OGDH), dihydrolipoyl succinyltransferase (EC 2.3.1.61; DLST), and the previously mentioned DLD (EC 1.8.1.4). Diaz and Komuniecki [86] showed that the enzyme from F. hepatica is not upregulated by calcium ions, in contrast to the mammalian OGDH [87,88]. This issue also needs further investigation from the point of view of the effect of inhibitory substances on OGDH to kill helminths.…”
Section: Discussionmentioning
confidence: 99%